A study on poverty among rural women in China - Huangang, Wang; Huanbo, Wang (International Journal of Social and Administrative Sciences, 2024)
This article mainly studies the issue of poverty among rural women in China. Through actual research and visits to two poverty-stricken counties in Northeast China - Inner Mongolia Autonomous Region, two key poverty-stricken counties in Northwest China - Gansu Province, two key poverty-stricken counties in Southwest China - Guizhou Province, and two severely impoverished counties in East China - Anhui Province, combined with existing excellent research literature, the main characteristics of rural impoverished women in China were finally summarized: the vulnerability, concealment, intergenerational transmission, and persistence of women's poverty The symbiosis of poverty and the derivative nature of poverty ideology. On this basis, this article summarizes the main causes of poverty among impoverished rural women in China: due to illness, education, lack of labor force, constraints of traditional concepts, and geographical factors; At the same time, it clarifies the role of rural women's poverty alleviation in the process of family poverty alleviation in China. Finally, this article outlines the significance of poverty alleviation for impoverished rural women in China from a sustainable perspective: alleviating family conflicts, reducing female crime rates, improving the quality of life for elderly women, effectively limiting intergenerational transmission of poverty, and improving national poverty alleviation effectiveness.